The emerging driving force of energy consumption in China: Does digital economy development matter? - Xue, Yan; Tang, Chang; Wu, Haitao; Liu, Jianmin; Hao, Yu (Energy policy, 2022)
Due to the benefits brought by progress in digital technology, the digital economy is profoundly changing the production and lifestyles of human beings, thus promoting the dual digital transformation of the energy supply side and demand side and having a profound impact on energy consumption. Based on 2011–2018 panel data on 30 provinces and 205 cities in China, this study empirically investigates the direct and indirect impacts of digital economy development on the scale and structure of energy consumption. The empirical results indicate that digital economy development promotes an increase in the scale of energy consumption and optimizes the structure of energy consumption. This result is still valid after robustness tests involving the selection of historical data as an instrumental variable (IV) and the “Broadband China” policy as a quasi-natural experiment. Mechanism analysis shows that digital economy development mainly impacts energy consumption by affecting economic growth, energy efficiency and the industrial structure. Moreover, the results of heterogeneity analysis and spatial model estimation indicate that the effects of digital economy development on energy consumption have obvious regional heterogeneity and spatial spillovers. •Digital economy development in various provinces and cities in China is estimated.•The influence of digital economy development on energy consumption is investigated.•Instrumental variable estimation and DID model are used to investigate causality.•Digital economy development influences energy consumption scale and structure.•Influential mechanism includes scale, structural, and technology effects.